2012
DOI: 10.4103/0971-4065.101242
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status in patients undergoing hemodialysis

Abstract: The aim of the study was to assess the periodontal status of patients among group of patients receiving hemodialysis in two super specialty renal institutes in the state of Gujarat. A cross-sectional study of 304 subjects, 152 subjects each in dialysis, and control group was conducted. Oral hygiene status was assessed using a Simplified Oral Hygiene Index, and periodontal status was assessed using the Community Periodontal Index (CPI) and Loss of Attachment (LOA) as per WHO methodology 1997. The dialysis group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
5
29
3
Order By: Relevance
“…Nine studies adjusted the dataset for potential confounders (eg, age, gender, smoking and DM) using multivariate analysis, and 6 of them showed significant results (Appendix A). Overall, 9 studies presented with a P‐ value, and 7 of them claimed that the prevalence of periodontitis in patients with CKD was significantly higher than without CKD ( P < .05) . The remaining 2 did not have such findings ( P > .05) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies adjusted the dataset for potential confounders (eg, age, gender, smoking and DM) using multivariate analysis, and 6 of them showed significant results (Appendix A). Overall, 9 studies presented with a P‐ value, and 7 of them claimed that the prevalence of periodontitis in patients with CKD was significantly higher than without CKD ( P < .05) . The remaining 2 did not have such findings ( P > .05) …”
Section: Resultsmentioning
confidence: 99%
“…Table describes the characteristics of 7 case‐control studies and 38 cross‐sectional studies on the non‐directional association, and lists them in reverse publication order . Among them, 24 had a statistical analysis, but 7 did not consider any confounding factors (Appendix A) .…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Maryam Baharvand, it was found that there is a meaningful relationship between age with oral dryness in the elderly (24)This study is likely to contradict the study because of differences in the studied population and research tools as well as the history of dialysis. (25,26,27,28). It is likely that factors such as the sample size and the difference in the duration of dialysis and other factors that affect the oral status of patients, such as the fluid used between the two dialyses and the number of dialysis per month are due to this difference.…”
Section: Discussionmentioning
confidence: 99%
“…CRF patients have medical, psychological and socioeconomic characteristics that may predispose them to dental problems. Oral health in dialysis and transplant patients tends to be poor, and they are more likely to develop diseases of the oral cavity, potentially increasing morbidity, mortality and affecting the quality of life of patients 1,14 . When pediatric patients suffer from renal disease they will have oral manifestations of the condition that will depend on the type of kidney disease, medication administered, specific conditions of the host and the age of the patient at the onset of the disease 28 .…”
Section: Oral Disordersmentioning
confidence: 99%
“…Ammonia causes an increased oral pH, which "protects" teeth 14,28 . Some studies have observed children with CRF and a high percentage of caries.…”
Section: Hernández Cmentioning
confidence: 99%